Earth Alms Tradition in Temulus Village: A Hadith Perspective on Historical and Spiritual Values - Aprilia Laila Khusna; Zulham Qudsi Farizal Alam; Arif Friyadi (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
This study aims to examine the practice in accordance with Islamic teachings and to understand the significance of the series of activities in this tradition as a means of preserving local culture while expressing gratitude to Allah SWT for the abundance of blessings and prosperity bestowed upon us. The research method employed is a descriptive qualitative approach, involving the collection of two types of data: primary and secondary data. Primary data was obtained through interviews, while secondary data was collected from literature reviews, websites, and other relevant sources related to the topic under discussion. The research findings reveal the existence of the Earth Charity tradition, which incorporates Islamic values and hadith, serving as a foundation for understanding religious social phenomena. In addition, the community's belief in sedekah bumi as a means of warding off evil reflects a harmonious blend of spiritual beliefs and local traditions. This article is expected to increase the knowledge and understanding of the community, especially among young people, so that we can continue to preserve and maintain our cultural heritage.